1996
DOI: 10.1002/(sici)1097-0185(199607)245:3<459::aid-ar2>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical studies on the expression and estrogen dependency of EGF and its receptor and C‐fos proto‐oncogene in the uterus and vagina of normal and neonatally estrogen‐treated mice

Abstract: There are distinct developmental changes in the distribution and estrogen sensitivity of EGF. Only further studies can prove or disprove the association between the earlier reported disturbed growth control mechanisms in the uterus of adult but neonatally estrogen-treated females and the increased levels of uterine EGF and c-fos. The present results do not seem to explain mechanisms involved in the origin of neonatally estrogen-induced cervicovaginal epithelial abnormalities, nor do they explain the earlier de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The role of EGFR in the steroid-independent time period of neonatal uterine growth, however, is less well established. While the expression of both EGF and EGFR has been reported in the uterus of neonatal mice, no functional data exist (2,3). Our findings of decreased EGFR transcript and protein in the stroma of Hoxa11 mutants point, for the first time, to the potential importance of EGFR in the proper development of the uterus in neonatal mice.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The role of EGFR in the steroid-independent time period of neonatal uterine growth, however, is less well established. While the expression of both EGF and EGFR has been reported in the uterus of neonatal mice, no functional data exist (2,3). Our findings of decreased EGFR transcript and protein in the stroma of Hoxa11 mutants point, for the first time, to the potential importance of EGFR in the proper development of the uterus in neonatal mice.…”
Section: Discussionmentioning
confidence: 54%
“…Expression studies have revealed several factors present in the developing uterus including epidermal growth factor (EGF), EGF receptor (EGFR), keratinocyte growth factor (KGF), KGF receptor, and estrogen receptors (2)(3)(4)(5)(6). The importance of these genes in the proper development of the female reproductive tract, however, has not been established.…”
mentioning
confidence: 99%
“…Nuclear staining might indicate the translocation of the transcription factors to its place of action. C-fos has been described in porcine and mouse endometrium (Dubois et al 1993;Falck and Forsberg 1996) and in preimplantation embryos of several species such as the pig, mouse and sheep (Müller et al 1982;Whyte and Stewart 1989;Pal et al 1993;Xavier et al 1997). In the sheep, some individual blastocysts of the same gestational stage exhibited jun and fos transcripts, while others did not (Wu 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the irreversible proliferation of the vaginal epithelium in neonatally estrogenized mice is probably attributable to an estrogen-independent persistent activation downstream of estrogen signaling in the stromal cells. Indeed, a high level of expression of epidermal growth factor (EGF) is maintained in the vaginas of neonatally estrogenized mice even after ovariectomy (Falck and Forsberg 1996).…”
Section: Introductionmentioning
confidence: 99%